Use of metrics in structuring state contracting processes; in the Colombian National Army (2020)
The Colombian national army, in its need to satisfy goods and / or services at the time of its pre-contractual stage, uses various statistical metrics, which makes a market study consistent with the reality between the supplier and the demander. The objective of this essay is to determine why the use of statistical metrics is important when obtaining a reference price in the market survey. To this end, the problem question is as follows: Why is the use of statistical metrics important to determine a reference price, in a market study in state contracting, through the modality of short selection in the National Army in Colombia? In this context, state contracting helps satisfy your acquisition of goods and / or services through necessity, financial studies, and both legal and technical supports